The spin on a baseball for eight different pitches thrown by an elite professional pitcher - Nagami, T.; Higuchi, T.; Kaosue, K. (Sports Performance, 2015)
We analyzed the spin on a baseball pitched by a professional pitcher, who utilized eight distinct, different types of pitches in official league games. In the experiments he pitched each of the eight pitches twice from an official pitching mound to a catcher. The video image of the pitched baseball from just before until 500 milliseconds after ball release was taken with a high-speed video camera at a rate of 1,000 frames per second. A special apparatus was used to obtain the direction of spin axis and the spin rate. Both values varied considerably depending on the type of pitch. In the four kinds of pitches which were thrown with a grip similar to that of the four-seam fastball, ball spin was altered by changing the direction of spin axis and/or orientation of the seams. The other three kinds of pitches thrown with a grip different from that of the four-seam fastball. These pitches had a slower speed and/or slower spin rate than the four-seam fastball. Moreover, the subject was able to throw these different pitches without changing the throwing motion as viewed by a batter. Mastery of these skills is what made him an elite pitcher with a long career.